(untitled) (Research, Society and Development, 2023)
Considering this issue importance, the present study aimed to elaborate a systematic review on biometeorological variables and thermal comfort indexes for poultry (broiler chicken, layer hens and broiler breeders). This systematic review was accomplished through search and selection of complete papers published on scientific journals, within three digital data banks (Scopus, Scielo and PubMed). The papers selection used criteria were publications on national and international journals, and papers containing data regarding performance and biometeorological variables or thermal comfort indexes. In the data bank created for this review, the broiler chicken category contributed with 64.29% of the papers, while layer hens appeared in 33.93% of the scientific reports, and broiler breeders in 1.78%. The temperature parameter was the biometeorological variable with 100.00% occurrence in the studies for the broilers and layer hens, nevertheless, within the 56 papers analyzed in this systematic review, only 25.00% of it calculated thermal comfort indexes. Based on this review, it is concluded that, despite the increasing evolution on paper publications regarding birds thermal comfort indexes, this issue still requires research attention, aiming the development of techniques that favor thermal comfort for poultry breeding.